Lessons Learned From Conducting Internet-Based Randomized Clinical Trials During a Global Pandemic. (28th December 2020) - Pullen, Matthew F; Pastick, Katelyn A; Williams, Darlisha A; Nascene, Alanna A; Bangdiwala, Ananta S; Okafor, Elizabeth C; Hullsiek, Katherine Huppler; Skipper, Caleb P; Lofgren, Sarah M; Engen, Nicole; Abassi, Mahsa; McDonald, Emily G; et al.
Abstract: As the severe acute respiratory syndrome coronavirus 2 pandemic evolved, it was apparent that well designed and rapidly conducted randomized clinical trials were urgently needed. However, traditional clinical trial design presented several challenges. Notably, disease prevalence initially varied by time and region, and the pockets of outbreaks evolved geographically over time. Coupled with an occupational hazard from in-person study visits, timely recruitment would prove difficult in a traditional in-person clinical trial. Thus, our team opted to launch nationwide internet-based clinical trials using patient-reported outcome measures. In total, 2795 participants were recruited using traditional and social media, with screening and enrollment performed via an online data capture system. Follow-up surveys and survey reminders were similarly managed through this online system with manual participant outreach in the event of missing data. In this report, we present a narrative of our experience running internet-based clinical trials and provide recommendations for the design of future clinical trials during a world pandemic. Abstract : The global SARS-CoV-2 pandemic presents novel challenges to conducting high quality randomized clinical trials. Internet-based clinical trials are a possible avenue for surmounting some of these challenges. Here, we offer some of the lessons learned from conducting such a trial.